Cerebrotendinous Xanthomatosis: Case Report on a Rare Genetic Disease - Chowdhury, Goutam; Kayasthagir, Pradip Kumar; Chowdhury, Abhijit (Journal of Chittagong Medical College Teachers’ Association, 2017)
Cerebrotendinous Xanthomatosis (CTX) is a rare inborn progressive lipid storage disorder of autosomal recessive inheritance pattern.The multisystem disease causes decreased bile acid synthesis alongside cholesterol and cholestanol deposition in various tissue sites. This case report focuses on describing a middle-aged Bangladeshi male patient presented chiefly with neurological symptoms of CTX who received treatment with Chenodeoxycholic Acid (CDCA. JCMCTA 2017 ; 28 (1) : 72 - 75